Investigation of curves set by cubic distribution of curvature - Ustenko, S. A.; Didanov, S. V.; Agarkov, O. YU. (Science and Transport Progress, 2014)
Purpose. Further development of the geometric modeling of curvelinear contours of different objects based on the specified cubic curvature distribution and setpoints of curvature in the boundary points. Methodology. We investigate the flat section of the curvilinear contour generating under condition that cubic curvature distribution is set. Curve begins and ends at the given points, where angles of tangent slope and curvature are also determined. It was obtained the curvature equation of this curve, depending on the section length and coefficient c of cubic curvature distribution. The analysis of obtained equation was carried out. As well as, it was investigated the conditions, in which the inflection points of the curve are appearing. One should find such an interval of parameter change (depending on the input data and the section length), in order to place the inflection point of the curvature graph outside the curve section borders. It was determined the dependence of tangent slope of angle to the curve at its arbitrary point, as well as it was given the recommendations to solve a system of integral equations that allow finding the length of the curve section and the coefficient c of curvature cubic distribution. Findings. As the result of curves research, it is found that the criterion for their selection one can consider the absence of inflection points of the curvature on the observed section. Influence analysis of the parameter c on the graph of tangent slope angle to the curve showed that regardless of its value, it is provided the same rate of angle increase of tangent slope to the curve. Originality. It is improved the approach to geometric modeling of curves based on cubic curvature distribution with its given values at the boundary points by eliminating the inflection points from the observed section of curvilinear contours. Practical value. Curves obtained using the proposed method can be used for geometric modeling of curvilinear contours of objects in different industry branches.